Análise bibliométrica sobre contabilidade ambiental no período de 2009-2019 - Nunes, Zennia Silva (Universidade Federal do Tocantins, 2021)
The objective of this work is to analyze the growth focused on publications on the theme "Environmental Accounting". For this purpose, a bibliometric analysis of the research published in the Scopus database was carried out between 2009 and 2019. For the data, the R software and the Bibliometrix software package are used. Among them, Rb has an organizational role and indicates the following metrics: the number of articles analyzed, the average number of citations per article, the number of authors, the number of co-authors and the most influential The author of, keywords most relevant, the annual scientific achievements on the topic, the countries with the greatest participation, etc. The results showed that 344 published articles from 790 authors were related to 187 sources. In the last ten years, mainly in the international environment, there has been a growing interest in the topic of environmental accounting, mainly in Italy, the United Kingdom and the United States.